EXPLORING AND DEVELOPING LOCAL WISDOM IN RELATION TO MARINE CONSERVATION IN THE BUNAKEN NATIONAL MARINE PARK - Pratiknjo, Maria Heny; Mambo, Rully; Sandiah, Nasrun (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The environment is a global concern, including within Bunaken National Park. Safeguarding biodiversity is crucial for sustainable use. However, conservation efforts still face challenges. A significant threat to forest ecosystems is illegal logging, fragmentation, and forest conversion. This study aims to comprehend the local wisdom of the Bunaken National Park community concerning marine conservation. The study employs a qualitative research method with an ecological anthropology approach. Data were collected by means of interviews, observations, and document analysis from local communities. The findings reveal several significant points: Firstly, the community actively engages in the marine conservation process through a participatory approach. Despite the initial clash of interests between fishermen and the national park management, a mutual understanding was eventually reached regarding marine protection zones, encompassing core and utilization zones. Secondly, religious leaders wield a pivotal role in conservation endeavors. They interact with formal leaders and the community during worship, encouraging marine environment protection and community involvement in trash cleanup and preservation of mangrove trees. Thirdly, local wisdom, knowledge, and values persist in people's daily lives. Despite the religious shift from traditional beliefs to Christianity and Islam, certain values endure, such as the correlation between celestial bodies (moon and stars) and agricultural and fishing activities. Fourthly, the Navy contributes to marine conservation by offering close supervision, influencing changes in the mindset and behavior of the neighboring community to safeguard mangrove forests and marine habitats while diminishing the risk of wave-related disasters during high tides.